Assessment of user fee system : implementation of exemption and waiver mechanisms in Tanzania : successes and challenges - Munishi, Victima (Health Economics Unit, 2015)
The aim of this study was to evaluate the implementation of exemptions and waivers and to support efforts to address current challenges and promote use of public sector health services. The study was conducted in Bagamoyo and Mtwara rural districts. A qualitative approach (in-depth interviews and focus group discussions) was used since it was considered appropriate for a study focusing on the perceptions, views, and experiences of users and providers.